Challenges to high-sustainable economic growth in Vietnam - Hoang Xuan Long; Hoang Lan Chi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The international world is currently making a lot of positive remarks about the prospects for Vietnam’s long-term economic growth. To properly recognize these statements, it is necessary to analyze some of the fundamental issues of high and sustainable growth in developing countries. There have been some notable transformations, including the transformation of the economic growth model, adaptation to global context fluctuations, conversion of FDI resources into domestic resources, shift from use and imitation to technological innovation, and switch from primarily sequential to primarily catch-up and primarily forward-looking development. The fundamental transformations explain the success and failure of some countries in maintaining high growth and indicate the specific task to be performed to achieve high– sustainable growth in Vietnam.